Managerial Practices and Student Performance: Evidence from Changes in School Principals - Adriana Di Liberto; Ludovica Giua; Fabiano Schivardi; Marco Sideri; Giovanni Sulis (Institute of Labor Economics (IZA), 2023)
We study how managerial practices of school principals affect student performance and aspirations. We link administrative data on secondary Italian students to the management scores of their school principals in 2011 and 2015 based on the World Management Survey methodology. The frequent turnover of school principals over this period allows us to causally interpret school-fixed-effect estimates. We find that management quality positively and substantially impacts standardized math and language tests and student desire to attend college. The comparison to pooled-OLS suggests that fixed effects correct for the downward bias arising from selection of better school principals into more difficult schools.
Keywords: L2; I2; M1; O32; 330; management; productivity; school principals; student outcomes